THE ROLE OF INTERACTIVE LESSONS IN PRIMARY EDUCATION - Shodiyev Fakhriddin Teshaevich, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
This article discusses the technology of interactive teaching in primary education.